ANALISIS KETERKAITAN ANTARA AGAMA DAN BUDAYA PADA MASYARAKAT VIRTUAL DI INDONESIA - Ade Yul Pascasari Katili (Jurnal Pustaka Ilmiah, 2018)
This paper aims to determine the acculturation between religion, culture and virtual society and the implementation of religion, and culture in virtual communities in Indonesia. The research methodology used is a conceptual approach by analyzing existing data through the study of literature relating to the focus under study. The literature used is primary and secondary sources, namely books and several journals that examine the same subject matter. The results of this conclusion are religion, culture, society is an important aspect that takes a leading role in creating a diversity of cultures of a nation. Pluralism that occurs comes from the acculturation process between these two aspects. The success of an acculturation model of culture and religion will be strongly supported by the development of information technology that affects its people to develop in the virtual realm or modernization. It is hoped that by understanding the acculturation process between religion, culture and virtual society, we are able to reduce the alkuturation failure of these aspects in order to create a harmonious society in the current era of modernization.